Dielectric Properties of Multiferroics in Next-generation Memory Devices - Le Hoang Nam; Nam Peng; Arnes Yuli Vandika (Research of Scientia Naturalis, 2024)
The advent of next-generation memory devices necessitates materials that exhibit superior dielectric properties. Multiferroics, materials that exhibit simultaneous ferroelectric and magnetic ordering, have emerged as promising candidates for enhancing memory device performance due to their unique attributes. This study aims to investigate the dielectric properties of various multiferroic materials and their implications for next-generation memory applications. The focus is on understanding how these properties can be optimized to improve device efficiency and functionality. A series of multiferroic samples were synthesized using sol-gel and solid-state methods. Dielectric measurements were conducted over a range of frequencies and temperatures to characterize their dielectric constant, loss tangent, and temperature dependence. Comparative analyses with traditional dielectric materials were performed to evaluate performance. The findings reveal that specific multiferroic materials exhibit significantly enhanced dielectric properties compared to conventional dielectrics. Notable improvements in dielectric constant and reduced loss tangent were observed, indicating potential for better energy storage and lower power consumption in memory devices. The research demonstrates that multiferroics possess advantageous dielectric properties that can be harnessed for next-generation memory devices. Continued exploration of these materials is essential for advancing memory technology and developing more efficient, high-performance devices in the future.